Leading leaders : how to manage smart, talented, rich, and powerful people - Salacuse, Jeswald W. (AMACOM, American Management Association, 2006)
A unique leadership challenge: the ability to manage other leaders.
Keywords: Leadership.; Elite (Social sciences); elektronické knihy; electronic books